2018
DOI: 10.1107/s1600576718002182
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic patterns in Philippine indigenous textiles

Abstract: The aim of this study was to analyze a representative sample of Philippine indigenous textiles in order to capture the range of symmetries and color symmetries present. This paper examines the existence of symmetries in finite designs, and classifies the plane-group and frieze-group symmetry types of the repeated patterns in woven textiles. The tendency of a particular symmetry to be more or less common than another can indicate relationships between the symmetries and the weaving technique or the culture that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Of course, all over the world, educators can find other interesting and unusual objects which are familiar to the students and which will reinforce their motivation and interest in symmetry. 20 , 21 , 45 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, all over the world, educators can find other interesting and unusual objects which are familiar to the students and which will reinforce their motivation and interest in symmetry. 20 , 21 , 45 …”
Section: Discussionmentioning
confidence: 99%
“…Some of the presented patterns can be also used in teaching the symmetry of layer or rod ornaments which can serve as a “bridge” between frieze or plane groups and space groups. Of course, all over the world, educators can find other interesting and unusual objects which are familiar to the students and which will reinforce their motivation and interest in symmetry. ,, …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the supplementary weft technique, the additional weft threads are made to float over warp threads in a planned sequence to create the design or pattern. If the supplementary threads extend from edge to edge, they are 'continuous', but if they only go back and forth in small areas where they are needed, they are 'discontinuous'' (De Las Pen ˜as et al, 2018).…”
Section: Two Methods Of Chok Weavingmentioning
confidence: 99%
“…One of the mathematical formulas that can be applied is crystallographic patterns. Some research about finding the crystallographic patterns for traditional clothes can be found in (De Las Peñas et al, 2018;Hobanthad & Prajonsant, 2021;Kartika et al, 2022;Libo-On, 2019;Vasquez et al, 2020). Another mathematical formula that can be used is Frieze groups (Davvaz, 2021).…”
Section: A Introductionmentioning
confidence: 99%